The appraisal model of remedial and enrichment activities integrated with the independent curriculum in vocational field - Suhendar Suhendar; Muhammad Yusro; Asnul Dahar Minghat; Cucu Sutianah; Bayu Rahmat Setiadi; Fitri Nur Mahmudah (Jurnal Pendidikan Vokasi, 2023)
Implementing remedial and enrichment strategies followed by modeling the weight of the appraisal is the goal to be achieved in this study. The ASSURE model in this study has been used to develop an appraisal model for remedial and enrichment activities integrated with the independent curriculum in the vocational field. The results showed that the peer tutoring strategy among students could optimize remedial and enrichment outcomes. The students have shown their ability in independent and collaborative learning. In remedial and enrichment activities, groups of enrichment students have been directed to help their friends to be successful in remedial. Students' success in the remedial process is the success of enriching other students and vice versa. Each student has received an appreciation of the value according to his effort. The progress of remedial students is 8% to 82%, with an average of 10%. This progress forms the basis for determining the final score for the remedial, intermediate, and enrichment groups as tutors. The difference between the remedial and enrichment appraisal weights was determined using mathematical model 1. The final score of students who become tutors is determined using the mathematical model 3. The three mathematical models above can calculate remedial, enrichment, and tutor results. The use of this model helps teachers or lecturers to be more objective in giving grades. Lecturers' appraisal of student learning outcomes has been carried out in a transparent, fair, and accountable following the differences in the potential competencies of each student. Students have followed the learning process, the assessment process has been carried out properly, the teacher's documentation is complete, and the teacher is more confident.